The association between duration of postnatal weight loss and neurodevelopment outcomes in very low birth weight infants - Ya-Chi Hsu; Chung-Yu Pan; Yi-Hsuan Lin; Ming-Chih Lin; Teh-Ming Wang (Pediatrics and Neonatology)
Background: Premature births account for around 11% of the world's live births. With the improvements in survival that have been achieved in recent years, the neurological outcomes of these infants have attracted greater attention. The aim of this study was to evaluate the association between postnatal weight loss and neurodevelopment outcomes of very low birth weight premature infants. Methods: This was a prospective cohort study that was conducted in a tertiary referral center. Premature infants of birth weight less than 1500 g born between October 2015 and January 2017 were enrolled. Perinatal-demographic characteristics, medical interventions, and nutrition records were collected. The Bayley III tests performed by licensed child psychiatrists at corrected ages 6, 12, and 24 months old were adopted as outcome measurements. Results: In total, 52 infants were enrolled. The mean birth weight was 1071 g and the mean gestational age was 29.0 weeks. According to the univariate analysis, the duration of postnatal weight loss had a significantly negative impact on motor outcomes at 12 and 24 months old. The negative impact remained robust after adjusting for confounding factors by multiple linear regression models. The effect of repeated measurement was further considered by generalized estimating equation (GEE) models. GEE models also demonstrated a negative association between the duration of body weight loss and motor scores. Conclusion: The duration of postnatal weight loss might have a negative influence on long-term motor development in premature infants. Further studies of nutrition status and motor development are needed to elucidate the precise underlying mechanism.